2020
DOI: 10.1051/0004-6361/202038224
|View full text |Cite
|
Sign up to set email alerts
|

Photometric detection of internal gravity waves in upper main-sequence stars

Abstract: Context. Massive stars are predicted to excite internal gravity waves (IGWs) by turbulent core convection and from turbulent pressure fluctuations in their near-surface layers. These IGWs are extremely efficient at transporting angular momentum and chemical species within stellar interiors, but they remain largely unconstrained observationally. Aims. We aim to characterise the photometric detection of IGWs across a large number of O and early-B stars in the Hertzsprung–Russell diagram, and explain the ubiquito… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
158
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(184 citation statements)
references
References 103 publications
(191 reference statements)
26
158
0
Order By: Relevance
“…Only the parameters fitted to the remaining cases, for which good and reliable fits could be achieved, are presented in Table 2. It is important to note that these values are fully compatible with those observed for massive OB stars (Bowman et al 2020).…”
Section: Red Noisesupporting
confidence: 82%
See 1 more Smart Citation
“…Only the parameters fitted to the remaining cases, for which good and reliable fits could be achieved, are presented in Table 2. It is important to note that these values are fully compatible with those observed for massive OB stars (Bowman et al 2020).…”
Section: Red Noisesupporting
confidence: 82%
“…With the advent of high-precision space-borne photometry, it has also been found that a number of massive OB stars display elevated signal levels at low frequencies, aka "red noise", in their photometric times series (e.g. Blomme et al 2011;Ramiaramanantsoa et al 2018;Rauw et al 2019;Bowman et al 2019Bowman et al , 2020. Our γ Cas stars are no exception, showing that these stars fit the typical behaviour seen for stars of similar spectral types.…”
Section: Discussionsupporting
confidence: 62%
“…The presence of pulsations is also related to the relatively large macroturbulence derived (see Sect. 5.1.2 Simón-Díaz et al 2017), since stars with larger pulsation amplitudes typically show larger macroturbulence (Bowman et al 2020). We also note that Rivinius et al (2020) demonstrate variability caused by nonradial gravity-mode pulsations using SMEI and TESS photometry, with such low-frequency photometric variability being common among massive stars (Bowman et al 2019).…”
Section: Medium-term Variability Of the Narrow-lined Primarymentioning
confidence: 51%
“…The line profiles of the narrow-lined primary are dominated by a "triangular" shape from a radial-tangential broadening profile (Gray 1973;Simón-Díaz & Herrero 2014). This implies that the dominant broadening mechanism is not rotation, but macroturbulent velocity (caused by non-radial pulsations, see Aerts et al 2009;Bowman et al 2020;and Sect. 3.4).…”
Section: Rotation and Macroturbulencementioning
confidence: 99%
“…The insensitivity of the stochastic variability to a star's metallicity together with the fact that evolutionary timescales predicted most stars were likely on the main sequence was concluded as strong evidence that the observed stochastic variability is likely caused by IGWs excited by core convection (Bowman et al, 2019b). More recently, Bowman et al (2020) demonstrated that the morphology of the IGWs in the frequency spectrum probes the evolutionary properties of the star, such as mass and radius. Furthermore, the amplitudes of IGWs in photometry were found to correlate with the macroturbulent broadening in the spectral lines of dozens of massive stars observed by the TESS mission (Bowman et al, 2020), with macroturbulence also having been associated with pulsations (Aerts et al, 2009;Simón-Díaz et al, 2010, 2017.…”
Section: Diverse Photometric Variability In Massive Starsmentioning
confidence: 98%